The Influence of Parenting Model in Character Building Pattern of Palembang Aviation Polytechnic Cadets - M. Indra Martadinata; Nining Idyaningsih; Minulya Eska Nugraha; Hana Fatiha (International Journal of Educational Review, 2024)
Cadets are another term for students who are under an official school. In one case, it was reported by the media that there was violence in the parenting pattern of educating cadets. As we know that in parenting patterns between official schools can differ from one school to another. In the official school of character education, the mandatory things that are instilled in cadets include neatness, discipline, responsiveness, responsibility, reliability, and the main thing is ethics. This research explains the suitability of parenting patterns at the Palembang Aviation Polytechnic in order to achieve the achievement of character education for cadets. The parenting pattern at the Palembang Aviation Polytechnic has proven that the parenting pattern adopted by caregivers and coaches makes the cadets of the Palembang Aviation Polytechnic produce tough, disciplined successors to the nation. Proven by analysis using SPSS with data that has been collected from questionnaires distributed to all cadets as a survey of the parenting patterns of cadets at the Palembang Aviation Polytechnic.